Rancang bangun alat pendeteksi formalin pada kuah bakso berbasis arduino uno - Wiradharma, Rendy (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2023)
The formalin detector is a device designed to assist in identifying the level of formaldehyde in food and beverages. Formalin is a chemical used as a preservative, but it can also be harmful to health if too much is consumed. In this design, we use the HCHO sensor as part of the formalin detection system.The HCHO sensor works by utilizing a chemical reaction between formalin and a catalyst to produce hydroxyl and carbon monoxide. This sensor is capable of detecting the concentration of HCHO and sending an electrical signal to the control module connected to the device. The control module will analyze the signal obtained from the sensor and display the results on the LCD screen located on the tool.This design offers an easy and efficient solution for detecting formaldehyde levels in food and beverages, so that people can ensure that the food and drinks they consume are safe from harmful chemicals.